RESEARCH FRAMEWORK ON THE SUITABLE DEVELOPMENT MODEL AND MECHANISM OF GREEN STTLEMENT IN THE YANGTZE RIVER DELTA - Z. Wang; Y. He; J. Ge (International Association of Lowland Technology, 2004)
By selecting a breakthrough point from the Green Settlement of towns and cities in the Yangtze river delta, which is of great significance to the sustainable development strategy for human sttlement in China, this research tries to integrate the enduring regional